2010
DOI: 10.1177/1753944710361731
|View full text |Cite
|
Sign up to set email alerts
|

β-blockers and risk of all-cause mortality in non-cardiac surgery

Abstract: Myocardial ischemia is a frequent complication in patients undergoing non-cardiac surgery and beta-blockers may exert a protective effect. The main benefit of beta-blockers in perioperative cardiovascular morbidity and mortality is believed to be linked to specific effects on myocardial oxygen supply and demand. beta-blockers may exert anti-inflammatory and anti-arrhythmic effects. Randomized clinical trials which evaluated the effects of beta-blockers on all-cause mortality in patients undergoing non-cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…42,68,70 Some reviewers have suggested that the harm associated with beta-blocker use in the POISE study resulted from an excessive dose. 73 A metaanalysis of studies of beta-blockers by a task force of the American College of Cardiology and the American Heart Association 68 showed, however, that the increased risk of stroke and death was qualitatively unchanged when the POISE data were omitted. Other authors have suggested that it is more appropriate to initiate beta-blockade weeks, instead of hours, before surgery.…”
Section: Interventions Targeting the Stress Responsementioning
confidence: 99%
“…42,68,70 Some reviewers have suggested that the harm associated with beta-blocker use in the POISE study resulted from an excessive dose. 73 A metaanalysis of studies of beta-blockers by a task force of the American College of Cardiology and the American Heart Association 68 showed, however, that the increased risk of stroke and death was qualitatively unchanged when the POISE data were omitted. Other authors have suggested that it is more appropriate to initiate beta-blockade weeks, instead of hours, before surgery.…”
Section: Interventions Targeting the Stress Responsementioning
confidence: 99%
“…Though the current data is insufficient to demonstrate benefits of beta-blockers, the literature suggests that peri-operative beta-blockers provide a benefit which is usually restricted to patients undergoing high-risk surgery. [3910]…”
Section: Discussionmentioning
confidence: 99%
“…Potential benefits of the use of beta-blockers after non-cardiac surgery include reduction in post-operative myocardial ischaemia and prevention of arrhythmias 35. One retrospective study involving 1,205 patients with COPD (diagnosed using symptoms and spirometry) undergoing major vascular surgery found that use of cardio-selective beta-blockers was associated with a lower 30-day mortality rate (OR 0.37, 95% CI 0.19 to 0.72) and a reduced longer-term risk of death (hazard ratio [HR] 0.73, 95% CI 0.60 to 0.88).…”
Section: Evidence On Beta-blockers In Copdmentioning
confidence: 99%